People's Participation in Community Forest Management - Shusan Shrestha; Gyan Bandhu Sharma; Subodh Bhattarai (International Journal of Science and Society, 2022)
The proposed study introduced the "People's Participation in Community Forest Management". This study was conducted on community forest of the central part of Nepal in Sindhuli district. The main objective of this study was to assess the participation of users group in forest management activities, decision making, benefit sharing mechanism and finding the factors that effect on people's participation. Primary data was collected through preliminary survey, questionnaire survey, focus group discussion and key informant survey. Secondary data was collected from concerned Division Forest Office (DFO), CFUGs operational plan, constitution of CFUGs, minutes, and documents from local government and non-government organizations. The qualitative and quantitative data was analysed using statistical packages SPSS, MS Excel. For qualitative analysis descriptive methods were used and the result was presented in different charts, tables and graphs. From the study, participation of forest users' group was high on forest product collection and distribution and low in plantation in forest management activities, decision making process satisfactory and benefit sharing mechanism was transparent and factors affecting for the participation of users' group was illiteracy and busy in farming. Therefore, this study is supportive for all who work for the improvement of users’ group participation in the community forest management.